Photopolymerization kinetics of methyl methacrylate with reactive and inert nanogels. (September 2018) - D'Ovidio, Tyler J.; Roberts, Rebecca M.; Gautam, Dixa; Marks, Zefram D.; Saraswathy, Manju; Stansbury, Jeffrey W.; Nair, Devatha P.
Abstract: The enhanced in situ photopolymerization kinetics of methyl methacrylate (MMA) to poly(methyl methacrylate) (PMMA) through the incorporation of both inert and reactive nanogel (NG) fillers under ambient conditions has been demonstrated. In addition to the polymerization kinetics, the physical and chemical properties of the prepolymeric NG were also utilized to tune the thermoplasticity and mechanical properties of the PMMA polymer network. The protocol followed in this study imparts superior MMA photopolymerization kinetics (≥ 60% double-bond conversion within 15 min for > 35 wt% nanogel loadings and ≥ 95% double-bond conversion in < 60 min for all NG concentrations) when compared with traditional polymerization mechanisms. PMMA remained a glassy material following the incorporation of both inert and reactive NG as demonstrated by the glass transition temperature (Tg ) of the ultimate networks. Network linearity is uncompromised following incorporation of inert NG additives, thereby preserving the thermoplasticity of the PMMA network. As the non-functionalized, inert NG content increases, the maintenance of thermoplasticity occurs at the expense of mechanical properties (10× reduction of maximum strength at 25 wt% loading). These effects are less pronounced when reactive nanogels are employed (no significant reduction of maximum strength at 25 wt% loading with minimal crosslinking). The incorporation of NGs enable high chemical tunability within linear polymer networks. Given the wide range of monomers available for the synthesis of NGs, the methodology detailed in this study offers a scheme for the optimization of linear networks for specific targeted applications, hitherto deemed unrealistic under established polymerization protocols.